Thyme Oil Enhances the Inactivation of Salmonella enterica on Raw Chicken Breast Meat During Marination in Lemon Juice With Added Yucca schidigera Extract - Kiprotich, Samuel; Mendonça, Aubrey; Dickson, James; Shaw, Angela; Thomas-Popo, Emalie; White, Shecoya; Moutiq, Rkia; Ibrahim, Salam A. (Frontiers in Nutrition, 2021)
Enteric pathogens such as Salmonella enterica can survive in low pH conditions and pose a food safety threat during marinating of raw poultry meat. A study was conducted to investigate the effectiveness of thyme oil for killing S. enterica on raw chicken during marination in lemon juice containing yucca extract. Samples of raw chicken breast were inoculated with a five-serovar mixture of S. enterica (~108 CFU/mL) and immersed for 2, 4, 6, and 8h in four lemon-based marinades at 22 °C: lemon juice alone (L), L with added 0.5% yucca extract (L+Y), L + Y and 0.5% thyme oil (L+Y+0.5%TO) and L+Y+1.0%TO. The L and L+Y served as controls. Survivors were determined by surface plating chicken homogenates on xylose-lysine tergitol-4 (XLT4) agar and XLT4 agar overlaid with non-selective agar (TAL) and counting bacterial colonies after 48 h of incubation (35°C). Marinades containing Y and TO significantly reduced initial viable populations of S. enterica compared to control (L and L+Y) solutions (P<0.05). Based on S. enterica survivors on TAL medium, the L and L+Y reduced initial populations by 1.12 and 1.42 Log CFU/sample respectively after 8h whereas, Log reductions caused by L+Y+0.5%TO and L+Y+1.0%TO, respectively, were 2.62 and 3.91 (P<0.05). Numbers of survivors were higher on TAL compared to XLT4 agar (P<0.05); however, the extent of sub-lethal injury caused by the marinades was not statistically significant (P>0.05). The death rate of S. enterica increased significantly (P<0.05) in the marinades containing TO (0.5% or 1.0%) compared to control (L+Y). Based on these results, thyme oil has good potential to increase the antimicrobial efficacy of lemon juice marinade against Salmonella on raw chicken breast and enhance the microbial safety of this popular poultry product.